Peningkatan minat dan kemampuan membaca metode membaca nyaring (reading aloud) pada siswa kelas I sdn setono 1 - Sri Rahayuningsih; Endang Sri Maruti; Vivi Rulviana (Universitas PGRI Madiun, 2026)
This study was motivated by the low reading interest and early reading ability of first-grade students at SDN Setono 1. The purpose of this study was to improve students’ reading interest and early reading ability through the implementation of the Reading Aloud method. This research employed Classroom Action Research (CAR) conducted in two cycles. The research subjects were 12 first-grade students of SDN Setono 1, consisting of 6 male and 6 female students. Data were collected through observation, questionnaires, reading tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of the Reading Aloud method effectively improved students’ reading interest and early reading ability. The percentage of students with good reading interest increased from 41.67% in the pre-cycle to 66.67% in Cycle I and reached 91.67% in Cycle II. Students’ early reading ability also improved, as indicated by the learning mastery percentage, which increased from 41.67% in the pre-cycle to 66.67% in Cycle I and reached 91.67% in Cycle II. The average reading score improved from 63.75 in the pre-cycle to 74.58 in Cycle I and 86.25 in Cycle II. Based on the findings, it can be concluded that the Reading Aloud method is effective in improving reading interest and early reading ability among first-grade students of SDN Setono 1.